The effect of Bi addition on the electrical and microstructural properties of SAC405 soldered structure. Issue 1 (3rd April 2020) - Soares, Delfim; Sarmento, Manuel; Barros, Daniel; Peixoto, Helder; Figueiredo, Hugo; Alves, Ricardo; Delgado, Isabel; Teixeira, José C.; Cerqueira, Fátima
Abstract : Purpose: This study aims to investigate the effect of bismuth addition (up to 30 Wt%) on the microstructure and electrical conductivity of a commercial lead-free alloy (SAC405) near the solder/substrate soldered joint. The system under study is referred in this work as (SAC405 + xBi)/Cu, as Cu is the selected substrate in which the solder was casted. The electrical resistivity of this system was investigated, considering Bi addition effect on the local microstructure and chemical composition gradients within that zone. Design/methodology/approach: Solder joints between Cu substrate and SAC405 alloy with different levels of Bi were produced. The electrical conductivity along the obtained solder/substrate interface was measured by four-point probe method. The microstructure and chemical compositions were evaluated by scanning electron microscopy/energy dispersive spectroscopy analysis. Findings: Two different electrical resistivity zones were identified within the solder interface copper substrate/solder alloy. At the first zone (from intermetallic compound [IMC] until approximately 100 μm) the increase of the electrical resistivity is gradual from the substrate to the solder side. This is because of the copper substrate diffusion, which established a chemical composition gradient near the IMC layer. At the second zone, electrical resistivity becomes much higher and is mainly dependent on the Bi content of the solder alloy. In both identified zones, electrical resistivity is affected by its microstructure, which is dependent on Cu and Bi content and solidification characteristics. Originality/value: A detailed characterization of the solder/substrate zone, in terms of electrical conductivity, was done with the definition of two variation zones. With this knowledge, a better definition of processing parameters and in-service soldered electronic devices behavior can be achieved.